Global gene expression profile in myelodysplastic syndromes using SAGE - Mendiburu, C. F. [UNESP]; Silva, W. A.; Ricci, O.; Bonini-Domingos, C. R. [UNESP]; Fett-Conte, A. C. (Genetics and Molecular Research, 2008)
The molecular pathogenesis of myelodysplastic syndromes (MDS) is poorly understood. In order to expand our knowledge of genetic defects in MDS, we determined the overall profile of genes expressed in bone marrow from patients with refractory anemia with excess blasts (RAEB) by serial analysis of gene expression (SAGE). The present report describes a partial transcriptome of RAEB bone marrow derived from 56,694 sequenced tags that provides information about expressed gene products. This is the first attempt to determine an overall profile of gene expression specifically in RAEB at diagnosis using SAGE, which should be useful in the understanding of the physiopathology of MDS and in identifying the genes involved. ©FUNPEC-RP.
Keywords: Gene expression profile; Myelodysplastic syndrome; Refractory anemia with excess blasts; Serial analysis of gene expression methodology